Accessibility and surgical outcomes of transumbilical single-port laparoscopy using straight instruments for hysterectomy in difficult conditions - Chen-Ying Huang; Kai-Yun Wu; Hsuan Su; Chien-Min Han; Pei-Ju Wu; Chin-Jung Wang; Chyi-Long Lee; Chih-Feng Yen (Elsevier, 2014)
Objectives: To evaluate the accessibility of transumbilical single-port laparoscopy for hysterectomy in difficult conditions. Materials and methods: This prospective observational study recruited patients with benign diseases who were scheduled for laparoscopic hysterectomy between March 2010 and October 2011 to undergo the transumbilical single-port approach with straight instruments and a laparoscope. Results: In total, 109 patients were included with a mean [± standard error of the mean (SEM)] age of 45.9 ± 0.4 years and mean body mass index of 23.9 ± 0.3 kg/m2. The yielded mean uterine weight was 403.4 ± 25.3 g, with 28 (25.7%) weighing ≥500 g, including four specimens >1000 g, and 44 (40.4%) needed concurrent adhesiolysis. The operative time was 117.2 ± 4.2 minutes, estimated blood loss was 270.3 ± 22.9 mL, and the postoperative hospital stay was 2.8 ± 0.1 days. Patients with a uterus weighing ≥500 g had a higher intraoperative blood loss in comparison with those with a uterus weighing <500 g (375.4 ± 55.3 mL vs. 234.0 ± 23.0 mL; p < 0.05) and a higher incidence of blood transfusion (17.9% and 6.2%, respectively). The single-port approach was abandoned in four (3.7%) patients with severe pelvic adhesion-an additional port was opened for extensive adhesiolysis. None of the patients with a voluminous uterus needed an additional port. There were no major intraoperative or postoperative complications. Conclusion: The single-port approach using straight, conventional laparoscopic instruments was feasible and safe in the majority of the patients undergoing hysterectomy, and was found to be accessible even in cases with a large uterus. The patients benefitted from this approach and had less abdominal wounds. However, patients with a voluminous uterus tended to have more intraoperative blood loss, and in some cases with severe adhesions, additional port(s) were required for surgical effectiveness.